DIFFERENCES IN FINANCIAL MANAGEMENT BEHAVIOR BETWEEN WORKERS AND GENERATION Z STUDENTS IN SURAKARTA - Maryana Angi Pratiwi; Umi Hanifah; Ety Meikhati (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study aims to analyze the differences in financial management behavior between Generation Z workers and students in Surakarta. The research focuses on differences in financial literacy, consumption behavior, and financial management. This study employs a quantitative approach, collecting data through a questionnaire administered to 200 respondents consisting of Generation Z workers and students. The sampling technique used was purposive sampling. Data analysis was conducted using validity, reliability, and normality tests, as well as an independent samples t-test, with the assistance of SPSS. The results indicate that there are significant differences in financial literacy and financial management between workers and college students. Workers have a higher level of financial literacy than college students. Meanwhile, there were no significant differences in consumption behavior. These findings suggest that experience and financial responsibility play a role in shaping Generation Z’s financial management behavior.